Effect of prenatal care quality on the risk of low birth weight, preterm birth and vertical transmission of HIV, syphilis, and hepatitis. - Debora Melo de Aguiar; Andréia Moreira de Andrade; Alanderson Alves Ramalho; Fernanda Andrade Martins; Rosalina Jorge Koifman; Simone Perufo Opitz; Ilce Ferreira da Silva (Public Library of Science (PLoS), 2023)
Background Averse birth-outcomes still affect newborns worldwide. Although high-quality prenatal care is the main strategy to prevent these outcomes, the effect of prenatal care based on Kotelchuck index combined with consultation contents is still unclear. Thus, this article to evaluate the effect of the quality of prenatal care (PC) process on birth indicators in a cohort of puerperaes who attended maternity hospitals in Brazilian western Amazon, city of Rio Branco, in the state of Acre, Brazil, in 2015. Methods This research was a hospital-based cohort study. The sample consisted of 1,030 women who gave birth in maternity hospitals in the city between April 6 and June 30, 2015. This research was a hospital-based cohort study. The sample consisted of 1,030 women who gave birth in maternity hospitals in Rio Branco between April 6th. and June 30th., 2015. Prenatal care was classified as fully adequate when started ≤4th month; ≥80.0-109% expected consultations for GA according to the Kotelchuck Index; ≥5 records of blood pressure, weight, GA, fundal height, ≥4 records of fetal heart rate, fetal movements or equivalent to 75% of the number of consultations; in addition to recording ABO/RH, hemoglobin, VDRL, urine, glucose, anti-HIV and anti-toxoplamosis during the 1st trimester. The evaluated outcomes were low birth weight (LBW), preterm birth and vertical transmission of human immunodeficiency virus (HIV)/hepatitis/syphilis. Differences between proportions were assessed using the X² test, and the crude and adjusted odds ratios (OR) (95% CI) were estimated using unconditional logistic regression. Results Overall cohort, the outcomes incidences were 8.8% for LBW, 9.2% for preterm birth, and 1.1% for vertical transmission (syphilis/HIV/hepatitis). Crude and adjusted OR showed that inadequate PC increased the risk statistically significant of LBW (ORcrude: 1.84; 95%CI: 0.99-3.44; ORadjusted: 1.87; 95%CI: 1.00-3.52), and preterm birth (ORcrude: 1.79; 95%CI: 1.00-3.29; ORadjusted: 3.98; 95%CI: 1.40-11.29). Conclusion The results draw attention to the importance of quality PC in reducing the risks of LBW, preterm birth, and vertical transmission of syphilis/HIV/hepatitis. Moreover, using this proposed quality prenatal care indicator based on Kotelchuck index combined with consultations contents adjusted by GA may accurately predict unfavorable outcomes.